2020
DOI: 10.1177/1098612x20920041
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic vertebral canal stenosis in cats: clinical features, diagnostic imaging findings, treatment and outcome

Abstract: Objectives The aim of this study was to describe the clinical features, diagnostic imaging findings, treatment and outcome in cats with thoracic vertebral canal stenosis (TVCS). Methods Medical records and imaging studies of cats with TVCS were retrospectively reviewed. Outcome was acquired from patient records and from owners or referring veterinary surgeons via a telephone questionnaire. For each case, breed-, age- and sex-matched controls were identified with CT imaging of the thoracic vertebral column. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Among these anomalies, the most frequent was vertebral canal stenosis owing to articular process hypertrophy (Figure 3). This condition has been reported in a case report of two cats 3 and a more recent case series of nine cats, 8 with a median age of 9 years reported by the latter study, which is slightly older compared with that in this study (7.3 years). The study by Gillespie and De Decker 8 also reported a higher incidence of thoracic canal stenosis in the cranial thoracic region, more specifically at T3-T4 and T4-T5.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Among these anomalies, the most frequent was vertebral canal stenosis owing to articular process hypertrophy (Figure 3). This condition has been reported in a case report of two cats 3 and a more recent case series of nine cats, 8 with a median age of 9 years reported by the latter study, which is slightly older compared with that in this study (7.3 years). The study by Gillespie and De Decker 8 also reported a higher incidence of thoracic canal stenosis in the cranial thoracic region, more specifically at T3-T4 and T4-T5.…”
Section: Discussionsupporting
confidence: 47%
“…In a recent study on a population of 43 cats, 5 intervertebral disc herniation was more prevalent in the lumbar vertebral column compared with the thoracolumbar region, with fewer cases of intervertebral disc extrusion cranial to the T11 vertebra, making the area of interest of our study an unusual location for developing disc herniation in cats. 8 With regard to the presentation, most of our cases presented a chronic and progressive clinical history. This is in agreement with the more common conditions diagnosed as, typically, neoplasia, and anomalies can present as chronic and progressive diseases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 8 In a more recent study, non-lymphoid neoplasia and IVDD were the most common causes of spinal diseases, and TVCS was the seventh most common. 1 In a case series of TVCS in cats, all cats included in the report were middle-aged or older; 3 hence, TVCS is considered one of the differential diagnoses of middle-aged or older cats presenting with a chronic, progressive, possibly painful T3–L3 myelopathy. Contrary to previous reports, the cat in the present report developed neurological signs caused by TVCS at a young age; thus, TVCS should be included in the differential diagnoses of young cats with progressive, painful T3–L3 myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In retrospective research on TVCS in cats, all cats were over 5 years and the median age was 9 years. 3 TVCS secondary to articular process hypertrophy in two cats and diffuse idiopathic skeletal hyperostosis (DISH) in one cat have been reported. 4 , 5 The age of the cats in these studies was ⩾9 years.…”
Section: Introductionmentioning
confidence: 99%